2022
DOI: 10.3389/fimmu.2022.859598
|View full text |Cite
|
Sign up to set email alerts
|

The Xbp1-regulated transcription factor Mist1 restricts antibody secretion by restraining Blimp1 expression in plasma cells

Abstract: Antibody secretion by plasma cells provides acute and long-term protection against pathogens. The high secretion potential of plasma cells depends on the unfolded protein response, which is controlled by the transcription factor Xbp1. Here, we analyzed the Xbp1-dependent gene expression program of plasma cells and identified Bhlha15 (Mist1) as the most strongly activated Xbp1 target gene. As Mist1 plays an important role in other secretory cell types, we analyzed in detail the phenotype of Mist1-deficient plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As the main advantage of mime-seq is to facilitate miRNA profiling in rare cell populations, it is important to assess its sensitivity. To this end, we used the Bhlha15 -Cre line for conditional activation of HENMT1 ∆C -T6B expression in plasma cells (PCs), as the Bhlha15 (Mist1) gene is specifically expressed in PCs within the hematopoietic system (Wöhner et al, 2022 ). Seven days after immunization with sheep red blood cells, GFP + PCs (CD138 + TACI + ) were isolated from the spleen of Bhlha15 -Cre R26 LSL-HenT6B/LSL-HenT6B mice by flow-cytometric sorting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the main advantage of mime-seq is to facilitate miRNA profiling in rare cell populations, it is important to assess its sensitivity. To this end, we used the Bhlha15 -Cre line for conditional activation of HENMT1 ∆C -T6B expression in plasma cells (PCs), as the Bhlha15 (Mist1) gene is specifically expressed in PCs within the hematopoietic system (Wöhner et al, 2022 ). Seven days after immunization with sheep red blood cells, GFP + PCs (CD138 + TACI + ) were isolated from the spleen of Bhlha15 -Cre R26 LSL-HenT6B/LSL-HenT6B mice by flow-cytometric sorting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells in Path I highly expressed several genes encoding heat shock proteins (HSPs), such as Hsp70 members ( HSPA1 and HSPA8 ) [ 39 ] and Hsp90 members ( HSP90AA1 and HSP90AB1 ) [ 40 ], which acted as important immunomodulators in antigen presentation and T cell activation [ 41 ]. Cells in Path II highly expressed the genes associated with antibody synthesis and humoral immunity, such as XBP1 [ 42 ] and MZB1 [ 43 ], and genes encoding immunoglobulins. In addition, PPI network analyses based on differentially expressed TFs of each path suggested that some genes might be the key regulatory TFs in B cell differentiation, such as STAT1 in Path II, MYC in Path I and JUN in Pre‐branch (Supplementary Figure S4C ).…”
Section: Resultsmentioning
confidence: 99%
“…As the main advantage of mime-seq is to facilitate miRNA profiling in rare cell populations, it is important to assess its sensitivity. As the Bhlha15 (Mist1) gene is specifically expressed in plasma cells (PCs) within the hematopoietic system 24 , we used the Bhlha15 -Cre line for conditional activation of HENMT ΔC -T6B expression in splenic PCs. Seven days after immunization with sheep red blood cells, GFP + PCs (CD138 + TACI + ) were isolated from the spleen of Bhlha15 -Cre R26 LSL-HenT6B/LSL-HenT6B mice by flow-cytometric sorting ( Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%